2008
DOI: 10.1029/2008gl035847
|View full text |Cite
|
Sign up to set email alerts
|

Extent of Hadley circulations in dry atmospheres

Abstract: [1] The subtropical terminus of the Hadley circulation is interpreted as the latitude poleward of which vertical wave activity fluxes (meridional eddy entropy fluxes) become sufficiently deep to reach the upper troposphere. This leads to a sign change of the upper-tropospheric divergence of meridional wave activity fluxes (convergence of meridional eddy angular momentum fluxes) and marks the transition from the tropical Hadley cell to the extratropical Ferrel cell. A quantitative formulation for determining th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 16 publications
5
77
0
Order By: Relevance
“…The high-albedo experiment has the strongest mean tropical circulation and also weakens most. The Hadley cell does expand under increased CO 2 , consistent with theory and modeling (Held and Hou 1980;Korty and Schneider 2008;Levine and Schneider 2015;Lu et al 2007); however, the widening is the same in all four experiments (28 latitude). Hence, the experimental setup induces variability in strength but not position of the Hadley cell.…”
supporting
confidence: 52%
“…The high-albedo experiment has the strongest mean tropical circulation and also weakens most. The Hadley cell does expand under increased CO 2 , consistent with theory and modeling (Held and Hou 1980;Korty and Schneider 2008;Levine and Schneider 2015;Lu et al 2007); however, the widening is the same in all four experiments (28 latitude). Hence, the experimental setup induces variability in strength but not position of the Hadley cell.…”
supporting
confidence: 52%
“…Frierson et al (2007) also found a poleward expansion with increased mean temperature. Korty and Schneider (2008) and Walker and Schneider (2006) found a poleward expansion with a prescribed increased dry static stability. A smaller increase in width of the Hadley cells with increased meridional temperature gradient was also found by Korty and Schneider (2008), Walker and Schneider (2006), and Frierson et al (2007).…”
Section: Hadley Circulationmentioning
confidence: 99%
“…Furthermore, recent studies using idealized simulations emphasized that the dry static stability increase in subtropics is especially crucial for the poleward expansion of the Hadley cells Walker and Schneider 2006;Korty and Schneider 2008). Therefore, to study the impact of the SST changes on the large-scale circulation, the dry static stability has been computed with the static stability parameter S p , defined as…”
Section: A Midtropospheric Vertical Velocitymentioning
confidence: 99%
“…This widening tendency is in qualitative agreement with Sobel and Neelin (2006), who found that increasing the horizontal moisture diffusivity in an axisymmetric model (analogous to increasing the transient-eddy moisture flux) resulted in a wider ITCZ. Transient eddies have previously been shown to modulate the strength of the Hadley circulation through their effect on the both the angular momentum and energy budgets (Singh and Kuang 2016) of the tropics, and are also important for the extent of the Hadley circulation (Korty and Schneider 2008;Levine and Schneider 2015). Although MSE divergence by transient eddies has been found to be an important term in the energy budgets of the eastern Pacific (Peters et al 2008) and the ITCZ in an idealized model (Nolan et al 2010), the quantitative relationship between transient eddies and the size of the ITCZ has not been demonstrated previously.…”
Section: ) Transient-eddy Component Deddymentioning
confidence: 99%